To Sew or Not to Sew? : Assessing the Welfare Effects of the Garment Industry in Cambodia - Mejia-Mantilla, Carolina; Woldemichae, Martha Tesfaye (World Bank, Washington, DC, 2017)
This paper uses the 2011 Cambodia Socio-Economic Survey to analyze the relationship between participation in the garment industry and household welfare. The analysis relies on propensity score matching estimators to investigate whether households that have at least one member employed in the textile and apparel sector are better off than those who do not participate in the garment industry, in terms of several monetary and non-monetary welfare indicators. The findings show that garment households are less likely to experience self-reported food insufficiency, and their children are more likely to be enrolled in school. Yet, the positive effect of the treatment is restricted to the bottom 40 percent of the consumption distribution, possibly due to the nature of garment jobs, and the fact that they represent an attractive alternative for the poorest households but not necessarily for the better-off. Using instrumental-variables, the analysis also shows that remittances originating from the textile and apparel sector relax household budget constraints, increasing expenditures in education, health, and investments in agricultural activities.